Pembuatan Sistem Informasi E-Commerce Untuk Unit Aktivitas Kerohanian Buddhis Universitas Brawijaya (UAKB UB) - Kevin Renjiro; Dian Eka Ratnawati; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Universitas Brawijaya Buddhist Spiritual Activity Unit (UAKB UB) is a Student Creativity Unit (UKM) located at Universitas Brawijaya which is a place for Buddhist students to do organization activity. There are various divisions in UAKB UB, one of which is the Logistics and Entrepreneurship division. The related division is having problems with sales due to the pandemic and entrepreneurship is only done offline. The division wanted to develop its entrepreneurship but was very limited by circumstances, moreover because the pandemic at that time greatly hampered the division's sales process. Based on these problems, researchers created an e-commerce information system which on the admin side has features for adding goods, making changes to goods, confirming transactions and verifying ktm. Meanwhile, on the side of buyers who have registered, they have the feature to transact to buy the desired item remotely. The development of this system uses the waterfall method, because all requirements have been defined at the needs analysis stage which produces 2 actors, 11 functional requirements and 1 non- functional. This system was developed using Laravel. Based on functional testing, both sides get a success rate of 100%.